PERAN SERTA PEMERINTAH DESA DALAM PENYELENGGARAAN PARIWISATA DESA DI KABUPATEN SLEMAN YOGYAKARTA - Jum Anggriani; Indah Harlina; Tetty Samosir (Jurnal Hukum dan Bisnis (Selisik), 2022)
The participation of the village government in the implementation of village tourism is expected to be able to prosper the village community. The purpose of this study was to determine the role of the village government in the implementation of tourism in the village of Sleman district. The research methods used are normative and empirical research methods. In this study, it can be seen that the village government in Sleman Regency has not participated in village tourism yet